2018
DOI: 10.1186/s12934-018-0992-x
|View full text |Cite
|
Sign up to set email alerts
|

High cell density fed-batch production of insecticidal recombinant ribotoxin hirsutellin A from Pichia pastoris

Abstract: BackgroundThe fungal ribotoxin hirsutellin A (HtA) exhibits strong insecticidal activity; however, efficient systems for expressing recombinant HtA (rHtA) are lacking. Here, we established an efficient heterologous expression system to produce large amounts of rHtA.ResultsRecombinant Pichia pastoris transformants with high levels of secretory rHtA were screened, and in a fed-batch reactor, rHtA was secreted at levels up to 80 mg/l following methanol induction, which was more than sixfold higher than that in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(50 reference statements)
0
2
0
1
Order By: Relevance
“…Methods for producing HtA using a recombinant strain of Pichia pastoris and fermentation in a bioreactor with a yield of 80 mg/L were developed. This allowed a better characterization to be achieved for this protein: its molecular weight (15.3 kDa), stability (high resistance to proteases and temperature), toxicity to Sf9 cells, and insecticidal activity against G. mellonella larvae were determined [ 230 ]. An analog of HtA, anisoplin, was found in M. anisopliae [ 231 ].…”
Section: Insecticidal Proteinsmentioning
confidence: 99%
“…Methods for producing HtA using a recombinant strain of Pichia pastoris and fermentation in a bioreactor with a yield of 80 mg/L were developed. This allowed a better characterization to be achieved for this protein: its molecular weight (15.3 kDa), stability (high resistance to proteases and temperature), toxicity to Sf9 cells, and insecticidal activity against G. mellonella larvae were determined [ 230 ]. An analog of HtA, anisoplin, was found in M. anisopliae [ 231 ].…”
Section: Insecticidal Proteinsmentioning
confidence: 99%
“…Olombrada et al [ 59 ] reviewed the potential biotechnological applications of these highly specific enzymes. Research completed by Li and Xia [ 60 ] showed the efficacy of ribotoxins as pest control agents either alone or conjugated with other compounds. This was used in experiments involving a recombinant form of the insecticidal ribotoxin hirsutellin A (HtA) produced from Pichia pastoris .…”
Section: Relevant Metabolites Produced By Fungimentioning
confidence: 99%
“…Разработан способ получения ХтА с использованием рекомбинантного штамма Pichia pastoris и ферментацией в биореакторе с выходом на уровне 80 мг/л. Это позволило полнее охарактеризовать этот белок: определить его молекулярную массу (15.3 кДа), стабильность (показана высокая устойчивость к протеазам и температуре), токсичность для клеток линии Sf9 и инсектицидную активность в отношении личинок G. mellonella (Li, Xia, 2018). Аналог ХтА -анизоплин -был обнаружен у M. anisopliae (Olombrada et al, 2017).…”
Section: грибные белкиunclassified